2006
DOI: 10.1149/1.2221865
|View full text |Cite
|
Sign up to set email alerts
|

An Advanced Sample Structure for Large-Grain Growth by Excimer Laser Crystallization

Abstract: We have developed an advanced sample structure for large-grain growth by excimer-laser crystallization of Si. More than 10μm long grains were grown laterally in a 50nm thick Si layer by phase-modulated excimer-laser annealing. A photosensitive SinormalOx capping layer prepared using a conventional plasma-enhanced chemical vapor deposition apparatus enables this longer lateral growth with lower irradiated intensity of laser light than those with the conventional SinormalO2 capping layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The authors have proposed a phase modulated excimer laser annealing (PMELA) method for position-controlled grain growth 6) and have investigated a method to increase the growth length. 7) In this paper, we report that the growth length per single shot can be increased markedly to 25 mm, which is sufficiently long for the fabrication of TFTs with conventional feature size.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The authors have proposed a phase modulated excimer laser annealing (PMELA) method for position-controlled grain growth 6) and have investigated a method to increase the growth length. 7) In this paper, we report that the growth length per single shot can be increased markedly to 25 mm, which is sufficiently long for the fabrication of TFTs with conventional feature size.…”
Section: Introductionmentioning
confidence: 93%
“…Because such TFTs can have no grain boundary that intersects the channel normally, carriers are rarely scattered by the grain boundary, resulting in high mobility and little fluctuation. The lateral growth phenomenon 3) observed in the excimer-laser crystallization method appears to be effective for such grain growth, and several methods [4][5][6][7] have been investigated. However, typical values of the excimer-laser-triggered lateral growth length reported to date are only 2 -3 mm per light pulse shot, and an inefficient step-and-repeat technique 5) is required for TFT fabrication on a large glass substrate, such as 550 Â 650 mm 2 , whereas the minimum resolution of photolithography is more than 1 mm in general.…”
Section: Introductionmentioning
confidence: 99%
“…Im et al have reported a rapid lateral grain growth ~5 μm by a single pulse irradiation of excimer laser with an energy just below the complete melting threshold energy without heating the substrate (14). Hiramatsu et al succeeded in spatially controlled lateral grain growth using a phase shift mask in order to make spatial distribution of the excimer laser intensity (15). Van crystallization method to control crystalline nucleation so called "μ-Czochralski" and succeeded in spatially controlled crystalline grain formation (16).…”
Section: Pulsed Excimer Laser Induced Crystallizationmentioning
confidence: 99%
“…Therefore, molten Si can crystallize more slowly, and consequently, grains that are larger than those of the no-SiO x -layer sample grow. 8) The thicknesses of the SiO 2 layers deposited below and above the a-Si layer are both 30 nm. These layers are inserted in order to avoid contamination of the a-Si layer.…”
Section: Unit Of Light Intensity Profilementioning
confidence: 99%